The Case Report of Fixed Prosthetic Treatments on a Cohen Syndrome Patient under General Anesthesia - Kitagawa, Takashi; Nakamura, Zenkou; Mayanagi, Akihiro; Yoshida, Takayoshi; Hasegawa, Shigeo (Nihon Hotetsu Shika Gakkai Zasshi, 1999)
The dental treatments of severely disabled patients who cannot understand the necessity of dental treatments are very difficult due to behavior problems. It is important to find solutions of oral hygienic problems for such patients who have muscle hypoactivity in the oral region and dislike teeth brushing. Removable prostheses are also not applicable to these patients because of lack of understanding and accidental swallowing. Therefore, treatment with a fixed prosthesis is effective. A Cohen syndrome patient was treated with an almost full fixed prosthesis having a small number of abutment teeth under general anesthesia at dental clinic of Tokyo Metropolitan Higashiyamato Medical Center for the Severely Disabled. The results were as follows: 1. In biting and occlusal adjustment, the mandible of the patient had to be guided to the proper mandibular position by the operator. It was effective to maintain the intercuspal position of upper and lower left second molar teeth during treatment. However, it was very difficult to judge whether the position guided to by the operator is appropriate. 2. Functional restorations including better posture, lip closure and swallowing were obtained after treatment.